(2x-5)=-6

Simple and best practice solution for (2x-5)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-5)=-6 equation:


Simplifying
(2x + -5) = -6

Reorder the terms:
(-5 + 2x) = -6

Remove parenthesis around (-5 + 2x)
-5 + 2x = -6

Solving
-5 + 2x = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 2x = -6 + 5

Combine like terms: -5 + 5 = 0
0 + 2x = -6 + 5
2x = -6 + 5

Combine like terms: -6 + 5 = -1
2x = -1

Divide each side by '2'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 9.5=v+2.8 | | 8x-6=3x+24 | | (2x-5)=6 | | 15x-8x=49 | | 12*c=108 | | 7y+8=-2y | | 2v+28=16+-4(v+7) | | -2(g+8)=64 | | -2-m=7 | | 4x^2=3x^2+9 | | 5(f-4)=-10 | | -5+5x=35 | | (x-2)=-2x-1 | | 8g-32=4g+16 | | X+17+4x=-29-4x-35 | | 1halfr+6=3-2r | | -10(s+3)=-71 | | (5x^3-6x^2+2x)+(-4x^2+3x)=42 | | 35x^2+76x+32= | | -10(s+3)=71 | | (x-5)=-6x-10 | | 3-2x^2=21 | | 10=-0.15x^2+3x | | t+10=7t+4 | | -8+3x=6+x | | 2-o=-42 | | (x-3)=-6x-17 | | -2+12=12 | | 3n+8-8=-3+2n | | x^2+47x=48 | | (x-3)=6x+17 | | 9.4=5.6-d |

Equations solver categories